Improvement of the technology of meat and meat containing products using mushroom half-finished product - Pasichnyi, Vasyl; Yastreba, Yulia; Herman, Nataliya; Geredchuk, Alina (My University, 2013)
The article is devoted to the aspects of scientific research and working out the technology of powder-like intermediate product and structured intermediate product from oyster mushrooms. The results of the using half-finished products from mushrooms in the technology of combined meat products and pastes of improved food quality were represented.
Keywords: product safety; technology; powder-like half-finished products from mushrooms; meat and meat containing products; безпека продукції; технологія; грибний порошкоподібний напівфабрикат; м'ясні та м'ясомісткі продукти; безопасность продукции; технология; грибной порошкообразный полуфабрикат; мясные и мясосодержащие продукты; кафедра технології м’яса і м’ясних продуктів